The Development Of Tin Oxide Based Catalyst For Environmental Emission Control - Wan Abu Bakar, Wan Azelee (Universiti Teknologi Malaysia, 2001)
Tin (IV) oxide (SnO2) has been identified as a potential catalyst in the treatment of toxic gases generated from vehicular emission and industrial activities. The presence of the first row transition metal oxides as dopants can increase its catalytic ability. In this study, tin (IV) oxide based catalyst with the addition of first and second dopants which comprise of Co(II), Co(III), Ni(II), Mn(II), Mn(IV), Cu(II) and Cr(VI) metal oxides were prepared by the modification of sol-gel method. The catalyst precursors and metal oxides dopants were prepared at various ratios and underwent various calcination temperatures. The catalytic ability of these catalysts were tested towards the oxidation of carbon monoxide (CO). Three catalysts, Co(II)-doped SnO2 (30:70) calcined at 400 °C, Ni(II)/Co(II)-doped SnO2 (0.10:29.97:69.93) and Mn(IV)/Co(II)-doped SnO2 (0.30:29.91:69.79) both at 600 °C calcination temperatures showed excellent catalytic activity. They completed the CO oxidation to CO2 at 175 °C, 150 °C and 190 °C respectively. The nitrogen adsorption analysis reveals that the best catalysts are in the form of pore mixture namely mesopore and micropore. The pores are identified as open cylindrical in shaped with pore diameter of 10 nm. Furthermore, the catalyst posses reasonably small particle size with high surface area. The XRD analysis illustrates the presence of SnO2 with tetragonal and Co3O4 with cubic phases, presumably act as the active site in the catalytic oxidation. The existence of cobalt oxide (in a mixture of +2 and +3 oxidation states) and the presence of Co2+-O and Co3+-O species further contribute to the excellent oxidation of CO as confirmed from the XPS analysis. However, both XRD and XPS analysis cannot detect the presence of second dopant probably due to very small quantity in the catalysts. Morphology studies by SEM illustrated the homogeneity of catalysts particle and showed irregular in shape. The TGA/DTG analysis shows that the reduction in the catalysts mass are maximum at the temperature lower than 400 °C accounts to the removal of surface molecules. It is supported by the FTIR analysis which proved that increasing calcination temperatures has enhanced the elimination processes of surface functional groups like the terminal, deformed mode and bridging hydroxyl. Consequently, the metal-oxygen (Sn-O) vibration mode becomes sharper and more significant. iv KANDUNGAN